The Effect of Independent Double Check Implementation against the Six Correction Principle in Preparation and Administration of Injected Medication on Inpatients X Hospital, West Java - Junita Maulina Manurung; Emiliana Tarigan; Emiliana Tjitra (Universitas STRADA Indonesia, 2021)
The study was conducted from March until June 2021. The number of nurses involved were: 39 first nurses and 33 second nurses. The research data were analysed using SPSS program version 25. The implementation of IDC on 5895 injected medication affected right time (p=0.000) and right documentation (p=0.041) in preparation of medication. IDC has a partial or simultaneous effect with the characteristics of the first nurse on the right dose and right time in preparation of drugs (p = 0.000). IDC also affects the right dose, right time and right documentation in administration of injected medication (p<0.05). The characteristics of the first nurse's education had a partial effect on right documentation in preparation and administration of drugs, and right time in administration of injected medication (p<0.05). Nurses' work experience also had a partial effect on right documentation in administration of injected medication (p= 0.001). IDC implementation reduces ME < 5%.